Utveckling av lösning för simulering av flexibla och konfigurerbara produktionssystem: Development of solution for flexible and reconfigurable production systems - Ingvarsson, Daniel; Johansson, Filip (My University, 2023)
The thesis was conducted at GKN Aerospace Sweden AB in Trollhättan during the spring of 2023. The purpose of the project was to investigate and demonstrate flexibility and reconfigurability in production cells through the development of a simulation model in Plant Simulation. The background of the thesis lies in the rapidly growing aerospace industry, where the demand for new aircraft is expected to double in the next 20 years. This increases the requirements of the production capacity, which lead to opportunities and challenges to meet the demand. The aim of the thesis was to develop an adaptable simulation model in Plant Simulation to demonstrate flexible and reconfigurable production. By performing simulations and drawing conclusions from the results, the work aimed to explore the flexibility and configurability of production cells and contribute to future industrial system solutions. The project was based on a production scenario from GKN Aerospace, where a micro-flow cell and CNC-machines were used to process and inspect parts. A simulation model based on this scenario was developed in Plant Simulation. The model had to be reconfigurable and adaptable during the simulation by changing process times, process sequences, volumes, personnel and working hours. The report provides information on the methods and workflow used in the study. Banks' model has been central in building a flexible and reconfigurable model. The results of the simulations demonstrate that a flexible and configurable model has been created. The requirements for demonstrating a flexible and configurable model have been achieved by building the model with easily modifiable tables and methods. The model visually demonstrates flexibility during the simulations but is also flexible in how it can be used and modified to achieve the user's goal